PENINGKATAN KEMAMPUAN GURU MADRASAH DALAM MEMBUAT APLIKASI ANDROID MELALUI PELATIHAN SELF-AWARENESS - Yudha Andana Prawira; Firman Nugraha; Muaripin Muaripin (FASTABIQ: JURNAL STUDI ISLAM, 2022)
This study aims to answer the challenges of teachers in increasing their competence in being creative during online learning. Because the Covid-19 pandemic condition requires an online learning process. One of the efforts made is to improve the competence of teachers in making android-based learning applications. The application used in this research is the one that refers to thunkable, which is one of the service providers for making android applications. This research was conducted through a one-shot case study approach with descriptive analysis. The results showed that the competence of madrasa teachers in making android-based applications increased after self-awareness-based training. The teacher's ability to increase both knowledge and skills is quite significant. This is indicated by a T-count of 0.072 with a level of trustworthiness of 95% which can be considered to have positive results on the implementation of training with a self-awareness approach. This ability indirectly has an impact on student motivation in online learning using teacher-made android-based applicationsKeywords: aplication based android, teacher ability, self-awareness